Marfan syndrome - T Sivasankari; Philips Mathew; Ravi David Austin; Sakthi Devi (Wolters Kluwer Medknow Publications, 2017)
Marfan syndrome (MFS) is the autosomal dominant-inherited multisystem connective-tissue disorder, with a reported incidence of 1 in 10,000 individuals and equal distribution in both genders. The main clinical manifestation of this disorder consists of an exaggerated length of the upper and lower limbs, hyperlaxity, scoliosis, alterations in the cardiovascular and pulmonary systems, and atypical bone overgrowth. Orofacial manifestations such as high-arched palate, hypodontia, long narrow teeth, bifid uvula, mandibular prognathism, and temporomandibular disorders are also common. Early diagnosis of MFS is essential to prevent the cardiovascular complications and treatment of orofacial manifestations, thus to increase the quality of life of the patient.